THE MAIN DIRECTIONS IN THE STUDY OF POLITICAL ELITES IN THE POST-CLASSICAL ITALIAN POLITICAL SCIENCE - Кирилл Сергеевич Кондрашев (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
Purpose Detection the main approaches to the definition of the political elites, their appearance and function in a democracy. Methodology of work The comparative method, structural and functional method. Results Marked changes in the methods of communication elites and masses, the emergence of new types of elites that meet the transforming needs of the masses, changing the structure of the political sphere in terms of postmodernism and globalization. Application of results The results can be applied in the process policy advice. DOI: http://dx.doi.org/10.12731/2218-7405-2013-5-27